Analiza sprememb kulturne krajine v občini Cerklje - Jamnik, Sonja (Gozdarski vestnik, 2007)
Land use in the cultural landscape of municipality Cerklje is characterised byintensive agriculture, settlements and infrastructure. A detailed comparisonof land use changes was carried out in the cadastral communities Cerklje and Zg. Brnik. Land use has changed significantly between the years 1826 and 2000; results show a decrease in arable land and pastures and an increase in forest areas. The largest increase is in building areas, mainly because of the growth of settlements and infrastructural development. The changes in social and economic conditions are the main reason for changes in land use.
Keywords: kulturna krajina; gozdovi; gozdne zaplate; raba tal; Cerklje na Gorenjskem